Behavioural Response to a Sudden Health Risk: Dengue and Educational Outcomes in Colombia - Kai Barron; Luis F. Gamboa; Paul Rodríguez-Lesmes (The Journal of Development Studies, 2019)
Epidemics tend to have a debilitating influence on the lives of directly afflicted families. However, the presence of an epidemic can also change the behaviour and outcomes of those not directly affected. This paper makes use of a short, sharp, unexpected epidemic to examine the behavioural response of the public to a sudden shift in the perceived risk to one's health and mortality. Our analysis finds that unafflicted school students change their behaviour substantially, affecting important life outcomes. In particular, we find that between 1.9 and 4.7 fewer students, out of a typical cohort of 47 pupils, sit their school leaving examination for every additional 10 cases of severe Dengue per 10 000 inhabitants in a municipality. We rule out several possible mechanisms, leaving an increase in the salience of the disease's risks as a plausible explanation for our findings.
Keywords: I12; I15; I20; D80; 330; health; health risks; education; human capital; Dengue; Colombia